Людина, яка мужньо долає життєві перешкоди (До 80-річчя від дня народження В.Т. Зінича) - Наулко, В. (Народна творчість та етнографія, 2006)
The article is dedicated to the 80th anniversary of Volodymyr Zinych, a famous ethnologist, who earned his degree in Rylskyi Institute of Art Studies, Folklore and Ethnology, National Academy of Sciences. He has done much for Ukrainian science and for his institute in particular. Scholar’s detailed biography is suggested for readers’ attention. V. Zinych’s scientific destiny is depicted thoroughly and vividly, beginning with his student and post-graduate years, following his researches as a mature scholar, and his activities in cooperation with the Government.